Different Surfactants-Assisted Hydrothermal Fabrication and Photocatalytic Properties of Bi2MoO6 for Methylene Blue Degradation under Simulated Sunlight Irradiation - Wenfeng Guo; Heping Li; Haisheng Ma; Weixiu Teng (Journal of Chemistry)
Bi2MoO6 single-crystallites were synthesized by a simple hydrothermal method in the presence of surfactant sodium dodecyl sulfate (SDS), polyvinyl pyrrolidone (PVP), or cetyl trimethyl ammonium bromide (CTAB). The samples were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), and ultraviolet-visible diffuse reflectance spectra (UV-vis DRS) techniques. The photocatalytic activities of the as-fabricated Bi2MoO6 samples were measured for the degradation of methylene blue (MB) under the Xe light illumination. It is shown that the introduction of surfactant have a crucial influence on the size and morphology of the Bi2MoO6 product. Among the as-fabricated Bi2MoO6 samples, the ones derived hydrothermally with CTAB showed outstanding photocatalytic activities for the addressed reaction under simulated sunlight irradiation, attributed to the ultrafine nanocrystals and the higher surface areas.